Advances in Nanomaterial-Based Microwaves and Infrared Wave-Assisted Tryptic Digestion for Ultrafast Proteolysis and Rapid Detection by MALDI-MS - Kumar Kailasa, Suresh; Wu, Hui-Fen (Combinatorial Chemistry & High Throughput Screening, 2014)
The unique physical/chemical properties of nanomaterials have significant impacts in electromagnetic waves (microwave and infrared waves)-assisted tryptic digestion approaches by using them as heat absorbers to expedite digestion and as affinity probes to enrich digested proteins prior to MALDI-MS analysis. We review recent developments in electromagnetic waves (microwaves and infrared waves)-assisted proteolysis using nanomaterials as heat absorbers and as affinity probes for analysis of digested proteins in MALDI-MS. New trends in ultrafast proteolysis (nonphosphoproteins- lysozyme, cytochrome c, myoglobin and bovine serum albumin (BSA); phosphoproteins- α- and β- caseins) using nanomaterials based microwaves and infrared (IR) waves assisted digestion approaches for rapid identification of digested proteins in the MALDI-MS.
Keywords: Infrared waves